An Escherichia coli strain for expression of the connexin45 carboxyl terminus attached to the 4th transmembrane domain - Kopanic, Jennifer; Al-Mugotir, Mona; Zach, Sydney; Srustidhar, Das; Grosely, Rosslyn; Sorgen, Paul (Frontiers in Pharmacology, 2013)
A major problem for structural characterization of membrane proteins, such as connexins, by nuclear magnetic resonance (NMR) occurs at the initial step of the process, the production of sufficient amounts of protein. This occurs because proteins must be expressed in minimal based media. Here, we describe an expression system for membrane proteins that significantly improves yield by addressing two common problems, cell toxicity caused by protein translation and codon bias between genomes. This work provides researchers with a cost-effective tool for NMR and other biophysical studies, to use when faced with little-to-no expression of eukaryotic membrane proteins in E. coli expression systems.